EXPLORING STUDENTS’ PERCEPTIONS OF DIGITAL MEDIA INTEGRATION IN EFL CLASSROOMS - Afritya Khairunisah; Titi Rokhayati; Abdul Ngafif (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2026)
This study examined how PowerPoint, YouTube, Canva, and Quizizz are used by an English teacher in face-to-face classroom instruction and how tenth-grade students perceive the impact of each platform on their interest, comprehension, motivation, and activeness in learning English. Drawing on Mayer's Cognitive Theory of Multimedia Learning and Self-Determination Theory, a descriptive qualitative design was employed, with data collected through classroom observations and semi-structured interviews involving eight purposively selected tenth-grade students at SMA Muhammadiyah Purworejo and SMA Muhammadiyah Kutoarjo, Purworejo Regency. Data were analyzed using the interactive model of Miles and Huberman through inductive coding and thematic analysis. The findings reveal that each platform served a distinct instructional function: PowerPoint for structured content delivery, YouTube for audiovisual input and pronunciation modeling, Canva for visual vocabulary instruction, and Quizizz as a gamified assessment tool. All eight students (8/8) reported increased interest and comprehension, seven of eight (7/8) reported motivational gains, and critical perceptions also emerged among four students (4/8) regarding internet disruption, alongside cognitive overload, time-pressure anxiety, and passive engagement during video viewing. The main contribution of this study is that the effectiveness of digital media integration depends on the alignment between platform affordances, pedagogical purpose, learner needs, and infrastructural support, not merely on the use of technology.